PENERAPAN LATIHAN RANGE OF MOTION (ROM) PADA KEKUATAN OTOT EKSTREMITAS DENGAN PENDERITA STROKE DI WILAYAH BINAAN PUSKESMAS GUNUNG PATI SEMARANG - Ns. Endro Haksara; Shafira Aliya Putri (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
The provision of passive ROM therapy in the form of range of motion exercises on the part of extremities experiencing weakness and decubitus, this motion exercise is very useful to avoid complications due to lack of movement such as joint stiffness.. This study aims to knowing the ROM description in nursing care in stroke patients with impaired physical mobility. This case study uses descriptive method. This case study was conducted in 12 – 28 april 2021 by comparing two respondents with the same case and given the same action. The results of the case study conclude the application of passive ROM techniques performed in non– hemorrhagic stroke patients there is a weakness in proximity there is an effective an ineffective,. The results of of increasing muscle strength on Subject I from 5151 to 5352, meanwhile in Subject II from 5151 to 5252, this is because the first patient and his family are very enthusiastic and eager to exercise independently while the second patient have an obesity and his family also have motivation but it still difficult due to the severity of the deases. Application of ROM in both non hemorrhagic stroke patients gave different responses.